2018
DOI: 10.3892/etm.2018.6539
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of local anesthetics on rabbit adipose‑derived mesenchymal stem cells during early chondrogenic differentiation

Abstract: Local anesthetics (LAs) are commonly used to provide peri-operative pain control in the peripheral joints. In the field of regenerative medicine, adipose-derived mesenchymal stem cells (ADMSCs) are gaining attention as a cellular source for repair and regeneration in degenerative diseases. However, previous studies have demonstrated that the commonly used drugs lidocaine, ropivacaine, bupivacaine and mepivacaine may be toxic to human chondrocytes, which has raised concerns over whether they exert similar negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Although the concentrations of different materials were consistent, it is still necessary to compare the influence of different concentrations of materials. Furthermore, the maximum observation time was 7 days, which referred to certain previous studies (17,23). Inevitable passaging of cells in vitro may limit the evaluation time.…”
Section: Discussionmentioning
confidence: 83%
“…Although the concentrations of different materials were consistent, it is still necessary to compare the influence of different concentrations of materials. Furthermore, the maximum observation time was 7 days, which referred to certain previous studies (17,23). Inevitable passaging of cells in vitro may limit the evaluation time.…”
Section: Discussionmentioning
confidence: 83%
“…These results were in consensus to the findings of Wu et al and colleagues, who investigated the effects of anesthetics on MSCs derived from rabbit adipose cells and concluded that 1% lidocaine showed little toxic effects when compared with other anesthetic agents at different concentrations. 10 Similarly, Shoshani et al and Berger et al studied the effects of lidocaine along with epinephrine and demonstrated that there was no effect on the viability of adipocytes after being exposed to this combination. 23 In line with the ideas of Celeste et al and colleagues, it was concluded that toxicity of lidocaine was dose and time-dependent, their study shed light on the fact that at low doses, lidocaine did not effect mitochondrial functions of fibroblast of the oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity of anesthetics is linked to their lipophilicity, thus lidocaine being less lipophilic makes it less toxic when compared to other amide anesthetic agents, validating their secure use in dental practice. 10 In case of clinical implications, a toxic anesthetic would augment the possibility of oral paresthesia, especially when administrating an inferior alveolar nerve block as studies report 89% chances of lingual nerve being involved. 12,24 Secondly, muscular stiffness is also linked to the myotoxic effects of anesthetics resulting in degenerative changes in masseter and medial pterygoid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAs are also administered into the shoulder joint to treat rotator cuff injuries and diseases [5]. In addition, fat aspiration for a cosmetic purpose or isolation of autologous adipose-derived stem/progenitor cells (ADSCs) routinely involves an administration of LAs [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%